1997
DOI: 10.1093/humrep/12.1.21
|View full text |Cite
|
Sign up to set email alerts
|

'Curing' empty follicle syndrome

Abstract: We report a novel method of rescuing empty follicle syndrome (EFS) and provide evidence that it is a drug-related problem rather than a clinical dysfunction. In a preliminary study we established that in EFS the serum beta-human chorionic gonadotrophin (beta-HCG) concentrations 36 h after HCG administration never exceeded 10 mIU/ ml. beta-HCG concentrations were thus used to confirm EFS when oocytes were not retrieved from one ovary after controlled ovarian hyperstimulation. The procedure was suspended leaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…Some have postulated that EFS is a drug-related problem rather than a clinical dysfunction (11,12), whereas others suggested that the occurrence of EFS in IVF can be attributed to a failure in [1] accurate timing of induction of final oocyte maturation, [2] properly scheduled ovarian hyperstimulation, or [3] instruction of patients and doctors (23). However, by differentiating between the false and genuine types, these suggestions become less relevant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some have postulated that EFS is a drug-related problem rather than a clinical dysfunction (11,12), whereas others suggested that the occurrence of EFS in IVF can be attributed to a failure in [1] accurate timing of induction of final oocyte maturation, [2] properly scheduled ovarian hyperstimulation, or [3] instruction of patients and doctors (23). However, by differentiating between the false and genuine types, these suggestions become less relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for EFS remain obscure, though many hypotheses have been put forward ranging from human error (6,(9)(10)(11) to pharmacologic problems (8,11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature describes two subtypes of EFS; the so called genuine EFSpresumably related to intrinsic ovarian factors -and false EFS, mainly related to pharmacological problems or human administration error. Several hypotheses as to the background of EFS after hCG triggering of final oocyte maturation in gonadotropin stimulated cycles have been proposed: early oocyte atresia due to a dysfunctional folliculogenesis in the presence of an apparently normal hormonal response [4], a biological abnormality in the supply of mature oocytes to be retrieved despite normal bioavailability of hCG [5], genetic factors such as LH/hCG receptor mutations [6, REF 22 from Yariz 2011], abnormalities in the in vivo biological activity of some batches of commercially available hCG or GnRHa [7], rapid clearance of hCG by the liver [7], pharmacological problems [5,8,9] and human error [5,7,10] -in particular inappropriate timing of the triggering bolus of hCG [8]. Moreover, advanced ovarian ageing is considered a risk factor for EFS recurrence, probably due to altered folliculogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…A rescue protocol can be used to salvage the cycle when the β-hCG concentration is <100 mIU/ml (Zegershochschild); Ndukwe et al, trying to predict EFS, stated that serum hCG levels were < 10 mIU/ml in cases of EFS but Stevenson and Lashen in a comprehensive review, offered that hCG levels of 40 mIU/ml should be the cutoff between normal to low hCG levels on the day of ovum pickup (OPU). 4,8,16 But In our patient in both cycles serum β hCG level was > 40 mIU/ml. Patients with EFS present a challenge to the treating physician.…”
Section: Discussionmentioning
confidence: 44%